Penanganan Cabin Fever melalui Terapi Kelompok Kognitif Perilaku pada Dewasa Muda selama Pandemi Covid-19 - Pradipta Christy Pratiwi; Fatma Kusuma Mahanani; Tri Esti Budiningsih (Universitas Andalas, 2022)
The Covid-19 pandemic is perceived as an unpleasant experience for many people. The various consequences of the Covid-19 pandemic have attracted the attention of various parties, one of which is mental health issues. The restrictions on social activities over a long period of time invoked among others the phenomenon of cabin fever. Cabin fever is a popular term that describes a person’s psychological responses such as demotivation or uncomfortable feelings. This study aims to examine the effectiveness of cognitive behavioral group therapy as an intervention effort for cabin fever in experimental quantitative research. Quantitative data was collected using the cabin fever phenomenon scale. Group therapy participants were 6 young adults aged 20-22 years. Friedman ANOVA test showed a significant difference between pre-test, post-test, and follow up. This showed that group therapy with a cognitive behavioral approach is effective reducing cabin fever symptoms in young adults.